Saccharomyces cerevisiae killer virus transcripts contain template-coded polyadenylate tracts. - Hannig, E M (1984)
The M double-stranded RNA component of type 1 killer strains of the yeast Saccharomyces cerevisiae contains an internal 200-base pair adenine- and uracil-rich region. The plus strands of this viral genomic RNA contain an internal adenine-rich region which allows these strands to bind to polyuridylate-Sepharose as tightly as do polyadenylated RNAs with 3'-terminal polyadenylated tracts of 70 to 100 residues. Internal template coding of an adenine-rich tract in positive polarity in vivo and in vitro transcripts of M double-stranded RNA may serve as an alternate method of transcript polyadenylation. The 3'-terminal residue of the in vitro m transcript is a non-template-encoded purine residue. The 5' terminus of this transcript is involved in a stem-and-loop structure which includes an AUG initiation codon, along with potential 18S and 5.8S rRNA binding sites. Except for the 3'-terminal residue, transcription in in vitro shows complete fidelity.